The rock [videorecording (DVD)] - Connery, Sean; Cage, Nicolas, 1965-; Harris, Ed, 1950-; Bay, Michael, 1964- (Buena Vista Home Entertainment, 1998)
All of San Francisco is taken hostage when a vengeful General seizes control of Alcatraz Island, threatening to launch missiles loaded with deadly poison gas.